Developing the 'Save the Earth!' E-Module as an ESD-Based Learning Tool to Enhance Sustainability Awareness and Critical Thinking among Indonesian Students (Journal of Science Learning, 2026)
This study aims to develop and evaluate the Save the Earth! e-module based on Education for Sustainable Development (ESD) to enhance students' critical thinking and sustainability awareness within the framework of the Pancasila Student Profile Project (P5). Utilizing the ADDIE development model, the e-module was designed around five interactive learning stages (Orientation, Contextualization, Real Action, Mini Exhibition, and Final Reflection) and integrated multimedia features to support project-based learning. The module's feasibility was assessed by expert validators, yielding average scores of 4.50 (media expert) and 4.60 (content expert), both categorized as "Very Feasible." Practicality testing conducted through small-group and field trials yielded average scores of 4.30 and 4.26, respectively, indicating that the module was "Very Practical" for classroom use. Effectiveness was measured using a one-group pre-test–post-test design. Statistical tests showed significant improvements (p 0.05) in both critical thinking and sustainability awareness. N-Gain scores revealed moderate improvement in critical thinking (0.67) and high improvement in sustainability awareness (0.74). These results indicate that the Save the Earth! e-module is a valid, practical, and effective educational tool. It holds strong potential for broader dissemination and future development, including integration with digital platforms and expansion to other P5 themes to promote transformative sustainability education.